2018
DOI: 10.1371/journal.pone.0191617
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of EV71 by curcumin in intestinal epithelial cells

Abstract: EV71 is a positive-sense single-stranded RNA virus that belongs to the Picornaviridae family. EV71 infection may cause various symptoms ranging from hand-foot-and-mouth disease to neurological pathological conditions such as aseptic meningitis, ataxia, and acute transverse myelitis. There is currently no effective treatment or vaccine available. Various compounds have been examined for their ability to restrict EV71 replication. However, most experiments have been performed in rhabdomyosarcoma or Vero cells. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 51 publications
1
24
1
Order By: Relevance
“…On the other hand, the most resistant cell line, HT-29, responded to curcumin with a significant increase of PKM1 isoform and probable increase of the PKM2 isoform. Our results are not the first to demonstrate the insensitivity of HT-29 to curcumin [32].…”
Section: Discussioncontrasting
confidence: 68%
“…On the other hand, the most resistant cell line, HT-29, responded to curcumin with a significant increase of PKM1 isoform and probable increase of the PKM2 isoform. Our results are not the first to demonstrate the insensitivity of HT-29 to curcumin [32].…”
Section: Discussioncontrasting
confidence: 68%
“…Though previous research has demonstrated that curcumin can inhibit human enterovirus 71 (EV71) replication in vitro [56], those studies were performed using Vero cells, which are non-human kidney epithelial cells. To better approximate the in vivo conditions of EV71 infection, Huang et al [20] evaluated curcumin against EV71 in HT29 human intestinal epithelial cells. Treatment with 10 µM of curcumin significantly reduced viral protein expression, genome replication and titer, and prevented EV71-induced cell death.…”
Section: Enterovirus 71mentioning
confidence: 99%
“…Treatment with 10 µM of curcumin significantly reduced viral protein expression, genome replication and titer, and prevented EV71-induced cell death. Time-of-addition assays revealed that curcumin did not affect viral attachment and entry, but it effectively inhibited protein expression during early stages of infection [20]. These effects appear to be at least partly due to the ability of curcumin to inhibit protein kinase C-δ (PKCδ).…”
Section: Enterovirus 71mentioning
confidence: 99%
“…Curcuma kwangsiensis ingredients have excellent antiviral effects against several viruses, such as hepatitis B virus (Hesari et al, ; Wei et al, ), hepatitis C virus (Tutik et al, ), EV71 virus (Huang, Chio, & Lin, ), porcine reproductive and respiratory syndrome virus (PRRSV; Du et al, ). We also wonder the possible antiviral effects of C. kwangsiensis ingredients against SGIV‐Gx.…”
Section: Discussionmentioning
confidence: 99%
“…Tutik et al () determined the antiviral activities of Curcuma genus against hepatitis C virus and further revealed a strong interaction between curcumin and 4GAG receptor; a protein involved in the entry step of HCV infection, which could be the mechanism of antiviral actions. Huang et al () demonstrated that curcumin could inhibit viral translation and increase host cell viability. Curcumin treatments also decreased the phosphorylation of protein kinase C delta (PKCδ), which plays a role in virus translation in EV71‐infected intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 99%